Government motivation-embedded return guarantee for urban infrastructure projects based on real options - Man, Qingpeng; Sun, Chengshuang; Fei, Yuesheng; Skitmore, Martin; Bai, Yong; Lu, Weizhuo (Journal of Civil Engineering and Management, 2016)
Governments usually guarantee the amount of investment income to private sector partners to encourage their participation in Public-Private Partnership urban infrastructure development projects, with the ‘float return on investment guarantee’ being the main method in use by the Chinese government today. The current problems with the float return on investment guarantee are analysed and a guarantee approach with embedded motivatio nal behaviour is presented as an alternative. A pricing method option is then introduced as the motivation-embedded return guarantee has similar characteristics to real options. From this, a valuation model is developed that provides the basis of a new systematic method for calculating the government guarantee value.